Effect and Mechanism of TFAM on Chemotherapy Resistance in Ovarian Cancer Cells Through Metabolic Reprogramming Regulation - Lingling FAN; Reziwanguli·WUBULI; Linglan LU; Lili HAN (Zhongliu Fangzhi Yanjiu)
ObjectiveTo investigate the role of mitochondrial transcription factor A (TFAM) in platinum-resistant ovarian cancer cells and its effects on metabolic reprogramming and sensitivity to platinum-based drugs MethodsThe mitochondrial function and metabolic characteristics of platinum-resistant ovarian cancer cells were analyzed. A TFAM-overexpressing cell model was established to assess its effects on platinum sensitivity, mitochondrial function, and aerobic glycolysis; and glycolytic enzyme and drug-resistant protein expression were analyzed. ResultsPlatinum-resistant ovarian cancer cells exhibited considerable mitochondrial dysfunction (reduced oxygen consumption rate) and enhanced aerobic glycolysis (increased extracellular acidification rate, glucose uptake, and lactate production). TFAM was downregulated in resistant cells. Meanwhile, TFAM overexpression significantly enhanced platinum sensitivity (P<0.01), restored mitochondrial function, and inhibited aerobic glycolysis. The expression levels of glycolytic enzymes and drug-resistant proteins were also downregulated (P<0.05). ConclusionTFAM downregulation is associated with suppressed oxidative phosphorylation and enhanced aerobic glycolysis in platinum-resistant ovarian cancer cells. TFAM overexpression can restore cellular dependence on oxidative phosphorylation and increase platinum sensitivity, suggesting that TFAM is a potential therapeutic target for reversing platinum resistance.